PEMBINAAN TKA/TPA AL-AMIN DI DUSUN MANIMPAHOI DESA SAOTENGNGA KECAMATAN SINJAI TENGAH - Mulkiyan; Nursyamsidar; K, Sulfikar; Surianti (LP2M Universitas Islam Ahmad Dahlan, 2023)
Coaching is defined as an educational effort, both formal and non-formal, that is carried out consciously, planned, directed and responsible in order to grow, guide and develop the basics of a balanced, intact and harmonious personality, knowledge and skills in accordance with their talents and abilities as a provision for then on his own initiative to add, improve and develop himself, his fellow human beings and the environment towards the achievement of optimal human dignity, quality and ability and an independent personality. This activity aims to improve the memorization of short suras and develop knowledge in reading the Qur'an to students.